Porcine circoviruses in Malaysia - Tan, Chew Yee; Thanawongnuwech, Roongroje; Ooi, Peck Toung (CAB International, 2023)
Over one decade since the first report, Malaysian porcine circovirus 2 (PCV2) molecular detection rates remain high at 83.78 and 83.54 for farm and sampled domestic pig population levels respectively. Clinically healthy finishers also showed a high detection rate of 94.74. Most notably, a major genotype shift from genotype PCV2b to PCV2d was observed. PCV2 antigen was also detected in the Malaysian wild boar population, sharing significant nucleotide identity similarities with PCV2 strains of domestic pigs. Porcine circovirus 3 (PCV3), which was discovered not too long ago in 2017, has been confirmed to be present among the Malaysian commercial pig population at a molecular prevalence of 41.67 at the farm level and 17.02 at the sampled domestic pig population level respectively. Most recently, PCV4 had been detected in Malaysia, albeit at a much lower molecular prevalence of 4.08. Both PCV4-positive samples originated from clinically healthy finishers. Phylogenetic analyses suggested the possibility of PCV3 and PCV4 being introduced by international trade activities. For practical and economic reasons, in the local Malaysian pig industry, field diagnostics of PCV2 cases generally rely on clinical and post-mortem findings, together with herd antibody titer and qPCR viremia titer. Currently, commercial PCV3 diagnostics service and vaccines are not available locally. With updated local PCV2 epidemiology, control and management efforts could be adapted into more effective strategies. A common management strategy for PCV2 challenge in farms could be applied for the time being to control potential PCV3 problems in the farms. As for PCV4, a larger number of field samples from cases of different clinical manifestations needs to be included to obtain a more accurate epidemiological picture.